PENGGUNAAN METODE PEMBELAJARAN MEMBACA MENULIS PERMULAAN (MMP) DI MI AL-IKHLAS MOSSO KECAMATAN SENDANA KABUPATEN MAJENE - Safirah, Nur; Shabir U, Muhammad; Hasrianti, Andi (Primer Edukasi Journal, 2025)
This research aims to: 1) Find out what methods are used in MMP learning, 2) Look for difficulties in using the initial reading and writing learning method, 3) Find out how to overcome difficulties in using the MMP learning method. This research uses a descriptive qualitative research method using a descriptive approach. phenomology. The results of the research show that: 1) The method used in learning to read and write beginning in school is the lecture, question and answer and assignment method, but educators have applied the Beginning Reading and Writing (MMP) learning method at the beginning of meetings with students, namely the syllabic method and the syllable method. SAS, the results of interviews with educators, namely that educators often only use 3 methods. However, educators used 2 MMP methods but in the author's perception when making observations it was seen that educators used the MMP method, namely the SAS method. 2) The difficulty in using the MMP method lies in the syllable method. Educators have difficulties because of differences in students' ability to recognize the letters of the alphabet due to environmental factors because students who do not know the letters of the alphabet at all are those who have not had time to sit in kindergarten school and conversely students who have understood and recognized the letters of the alphabet are those who have had the opportunity to attending kindergarten school. The results of interviews with educators were that educators had difficulty using the question and answer method because there was no response back from students. As for the responses of other educators, there are not too many difficulties in using learning methods, precisely because there is no learning media which causes difficulties in using learning methods. 3) The way to overcome difficulties in using learning methods is that educators are expected to do new things in the classroom, such as using simple learning media which the author did when using the SAS method with the help of drawing media and a piece of paper. The implications of this research are to increase understanding of the use of the MMP method, support curriculum development, increase learning effectiveness